Passos e espaços: casas e universo simbólico de ex-colonos em Minas Gerais - Linhares, Elizabeth Ferreira (1998)
The main finality of this study is to analyse the houses built by a group of rural workers, ex- colonos, after their movement from roça to town, in a process proportional to their own reconstruction as individuals. The material and symbolical construction of their houses was considered as result of the different conditions historically constituted and faced by the agents through their own lives. By this point of view, the casas de colono were focused as representative of an anterior lived reality and as referency model from which the actual houses built by these workers in town have been idealised. So, the meaning of their spatial/ formal conceptions must be considered as much as the main changes elaborated in the domestic space and the esthetic values of the group during this movement.